ANALISIS PENGGUNAAN QRIS SEBAGAI ALAT TRANSAKSI DI KALANGAN GEN Z - Vina Maudina; Adhisa Nabila; Dilla Novi; Shalva Marlina; Hani Hatimatunnisani (Jurnal Sosio dan Humaniora (SOMA), 2026)
This study aims to analyze the use of QRIS (Quick Response Code Indonesian Standard) as a digital payment method among Generation Z. The type of research used is quantitative with a descriptive method. A total of 46 respondents were randomly selected using a questionnaire. The results of the study indicate that ease of use and transaction speed are the main factors driving the intensity of QRIS use by Gen Z, while security and fast response to complaints are other supporting factors. These findings provide valuable insights for digital payment system developers and business actors to optimize marketing strategies and develop QRIS-based services to better reach the Gen Z segment.